Cardiac Drugs in Pregnancy - Sliwa, Karen; Anthony, John.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
In the western world, the risk of cardiovascular disease in pregnancy has grown due to the increasing age at the first pregnancy and the worldwide obesity epidemic leading to early diabetes and hypertension. As a result more women are requiring drug therapy during pregnancy  and some data has shown an altered pharmacodynamic profile in pregnant women when compared to the non-pregnant population. Cardiac Drugs in Pregnancy presents up-to-date research for the treatment of cardiovascular disease during pregnancy, and  discusses the most important indications of drug usage in pregnancy and postpartum. The book aims to assess the potential risk of drugs and their possible benefit against each other, making it an essential read for a wide range of health professionals involved in cardiac drug therapy in pregnancy.
Introduction -- General principles and guidelines -- Management of Hypertension -- Management of Heart Failure -- Management of  coronary artery disease & Arrhythmia -- Anticoagulation in Pregnancy -- Obstetric drugs in management if Cardiovascular disease -- Pregnancy anaesthesia in patients with cardiovascular disease.
Keywords: Cardiology; Obstetrics; Maternal and child health services; Pharmacotherapy; Cardiology; Obstetrics/Perinatology/Midwifery.; Maternal and Child Health; Pharmacotherapy